Cyclic Damage Accumulation in the Femoral Constructs Made With Cephalomedullary Nails - Hamandi, Farah; Whitney, Alyssa; Stouffer, Mark H.; Prayson, Michael J.; Rittweger, Jörn; Goswami, Tarun (Frontiers in Bioengineering and Biotechnology, 2021)
Background: The purpose of this study was to evaluate the risk of periprosthetic fracture of constructs made with long and short nails. The nails were made with titanium alloy (Ti-6Al-4V) and stainless steel (SS 316L). Methods: This research comprised of twenty-eight pairs of cadaveric femora that were randomized and implanted with four types of fixation cephalomedullary nails resulting in 4 groups. These constructs were cyclically tested in bi-axial mode for up to 30,000 cycles. All the samples were then loaded to failure to measure failure loads. Three frame works were carried out through this investigation, which are Michaelis-Menten modeling, phenomenological modeling, and probabilistic Monte Carlo simulation. Findings: Damage accumulation resulting from bi-axial cyclic loading in terms of construct stiffness was represented by Michaelis-Menten equation, and the statistical analysis demonstrated that one model can explain the damage accumulation during cyclic load for all four groups of constructs (P = 0.64). A two-stage stiffness drop was observed. The short stainless steel had a significantly higher average damage (0.94) than the short titanium nails (0.90, P = 0.023). Long titanium nail group did not differ substantially from the short stainless steel nails (P = 0.063). Results showed gender had a significant effect on load to failure in both torsional and bending tests (P =0.025 and P <0.001, respectively). Interpretation: Using Kaplan-Meier survival analysis supports the use of short titanium cephalomedullary nail. We recommend that clinical decision should take age and gender into consideration in the selection of implants.